2016
DOI: 10.1016/j.amepre.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Intervention to Alter Skin Cancer Risk Behaviors in Young Adults

Abstract: Introduction Skin cancer is the most common cancer, and its incidence is increasing. Young adults expose themselves to large amounts of ultraviolet radiation (UV) and engage in minimal skin protection, which increases their risk. Internet interventions are effective in modifying health behaviors and are highly disseminable. The current study's purpose was to test an Internet intervention to decrease UV exposure and increase skin protection behavior among young adults. Study design RCT conducted in 2014, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
72
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 76 publications
1
72
1
4
Order By: Relevance
“…Interventions have targeted young adults generally and those with any history of indoor tanning using used web- and print-based education to address perceived risks and benefits of tanning and appearance-based motives (38, 5962). Although interventions aimed at affecting perceived risks and benefits of health behaviors have promising effects generally (26, 63) and in some studies of indoor tanning (61, 64), our findings suggest this approach alone may be insufficient to promote behavior change among young adults endorsing indoor tanning dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions have targeted young adults generally and those with any history of indoor tanning using used web- and print-based education to address perceived risks and benefits of tanning and appearance-based motives (38, 5962). Although interventions aimed at affecting perceived risks and benefits of health behaviors have promising effects generally (26, 63) and in some studies of indoor tanning (61, 64), our findings suggest this approach alone may be insufficient to promote behavior change among young adults endorsing indoor tanning dependence.…”
Section: Discussionmentioning
confidence: 99%
“…One young adult trial involving a tailored interactive web program 46 ing, or standard mailings) found significant increases in selfreported skin self-examination compared with control conditions. Odds ratios for skin self-examination in intervention groups compared with control groups ranged from 1.16 to 2.64, with absolute differences in rates of skin self-examination ranging from 3.2% to 24.0% in favor of the intervention groups ( Figure 5).…”
Section: Adultsmentioning
confidence: 99%
“…In that trial of online education for young adults (n = 965; 86% with fair skin), the proportion of participants reporting red or painful sunburn in the past month decreased more markedly from baseline to 3 months in the tailored interactive web program group compared with 2 other groups (54.5% to 26.3% in the tailored interactive web program group; 51.5% to 38.2% in the public website group; 56.3% to 41.2% in the assessment-only control group; P = .01 for comparison of intervention vs assessment only, between-group difference not reported). 46 One trial (n = 1356) of counseling and promotional materials to encourage skin self-examination assessed skin cancer outcomes at 12 months and found no difference in numbers of cancers and atypical nevi detected in intervention and control groups.…”
Section: Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 12 months post randomisation, the sun protection group had significantly greater improvement in their SPH index compared to control [16] and building behavioural capacity (e.g., obtaining information and receiving reminders) was the most valued aspect of the messages [28]. Heckman et al 2016 recently reported significant decreases in UV exposure and increases in SPH index 3 and 12 weeks after baseline for participants who received a tailored interactive multimedia internet intervention program (UV4.me) [29]. These studies are illustrating that further improvements to the technology platforms are needed to reduce the sunburn prevalence in young adult populations.…”
Section: Discussionmentioning
confidence: 99%